2006
DOI: 10.1002/nbm.1091
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient histograms may predict low‐grade glioma subtype

Abstract: The subtypes of glioma are known to have different prognosis and response to treatment. The purpose of this work was to investigate whether apparent diffusion coefficient (ADC) histograms of untreated low-grade astrocytomas and oligodendrogliomas exhibit different characteristics due to their biological differences, and whether a diagnosis of tumour subtype can be made at presentation using the histogram alone, which, if possible, would have an impact on clinical practise. Fifteen patients with astrocytoma (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
96
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 23 publications
6
96
2
Order By: Relevance
“…Oligodendroglial tumours with intact 1p/19q were more likely to have a higher maximum and histogram ADC and a greater ADC transition coefficient (ATC) (Figure 5e,f). Similarly, Tozer et al [172] have reported that low-grade oligodendrogliomas had a lower ADC histogram than astrocytomas. These differences may reflect the cellularity of these tumours, as astrocytomas have a tendency towards lower cell density and to be more cystic than oligodendrogliomas, whereas tumours with intact 1p/19q are more likely to show infiltrative growth patterns [12].…”
Section: P/19q Genotypementioning
confidence: 84%
“…Oligodendroglial tumours with intact 1p/19q were more likely to have a higher maximum and histogram ADC and a greater ADC transition coefficient (ATC) (Figure 5e,f). Similarly, Tozer et al [172] have reported that low-grade oligodendrogliomas had a lower ADC histogram than astrocytomas. These differences may reflect the cellularity of these tumours, as astrocytomas have a tendency towards lower cell density and to be more cystic than oligodendrogliomas, whereas tumours with intact 1p/19q are more likely to show infiltrative growth patterns [12].…”
Section: P/19q Genotypementioning
confidence: 84%
“…The histographic analysis approach has been applied mainly in brain imaging. For example, Tozer et al (33) showed that ADCs below the 50th percentile histographic mode and skewness allowed discrimination between astrocytomas and oligodendrogliomas. In body imaging, Kyriazi et al (34) showed an increase in ADCs and a later decrease in skewness and kurtosis in response to chemotherapy in patients GENITOURINARY IMAGING: Myometrial and Lymphovascular Invasion and Endometrial Tumor Grade Nougaret et al with metastatic ovarian and primary peritoneal cancer.…”
Section: Author Contributionsmentioning
confidence: 99%
“…The apparent diffusion coefficient (ADC) can then be calculated from the DWI images (11). Tozer et al (12) suggested an apparent diffusion coefficient histogram analysis as a possible method to predict low-grade glioma subtypes. Khayal et al (13) showed a significant difference in median ADC values between ODs and ACs, with a large range of values within each lesion.…”
mentioning
confidence: 99%